An An Analysis of Jameson’s Double Consciousness in the Novel “Confessions of a Teen Age Hermaphrodite” - Hina Naz, Hina Naz; Dr. Saima Manzoor (Journal of Peace, Development and Communication, 2023)
Intersex individuals are grieved with elimination and deprivation. It has been a general observation that they are destined to remain unknown or low-caste. The societies do not provide them the opportunities to fulfill their basic needs, but rather add to their miseries and despairs. The present study tends to analyze the role of other people in the growth of double consciousness of intersex through the application of Du Bois’ theory of Double Consciousness to the intersex character of Jameson from the novel “Confessions of a Teen Age Hermaphrodite”. By adopting the qualitative approach and through textual analysis, the study interestingly highlighted that not only harsh, rigid, and degrading attitudes but sometimes care and affection of people also cause double consciousness of intersex. Moreover, it was also noted that some people do not deliberately become the source of intersex’ double consciousness, it is done unintentionally.